2015
DOI: 10.1093/toxsci/kfv235
|View full text |Cite
|
Sign up to set email alerts
|

2,3′,4,4′,5-Pentachlorobiphenyl Induces Inflammatory Responses in the Thyroid Through JNK and Aryl Hydrocarbon Receptor-Mediated Pathway

Abstract: Polychlorinated biphenyls (PCBs) are durable and widely distributed environmental contaminants that can compromise the normal functions of multiple organs and systems; one important mechanism is the induction of inflammatory disorders. In this study, we explored the influences of 2,3',4,4',5-pentachlorobiphenyl (PCB118) on inflammatory responses and its underlying mechanisms in the thyroid. Wistar rats were administered PCB118 intraperitoneally at 0, 10, 100, and 1000 μg/kg/d, 5 days a week for 13 weeks; rat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…Indeed, previous studies using the FRTL-5 cells have demonstrated that quercetin has anti-thyroid effects inhibiting the expression of the thyroid-specific genes NIS, TSHR, TPO and TG [10,11]. At least some of these effects may be mediated by AP-1 activation, as suggested by the observation that jun activation is associated with a decrease of NIS gene expression [48]. Of course, more detailed studies are needed to know which factors of the AP-1 family are activated by quercetin in thyroid cells and how they interact with the regulatory regions of the genes involved.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous studies using the FRTL-5 cells have demonstrated that quercetin has anti-thyroid effects inhibiting the expression of the thyroid-specific genes NIS, TSHR, TPO and TG [10,11]. At least some of these effects may be mediated by AP-1 activation, as suggested by the observation that jun activation is associated with a decrease of NIS gene expression [48]. Of course, more detailed studies are needed to know which factors of the AP-1 family are activated by quercetin in thyroid cells and how they interact with the regulatory regions of the genes involved.…”
Section: Discussionmentioning
confidence: 99%
“…Calibrations always gave an R 2 above 0.96 and allowed the quantification of SP and IBs. This method has been used in over 700 publications to date and is known to give precise data (e.g., Matusica et al 2016 ; Wahlang et al 2016 ; Xu et al 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, as a highly conserved pathway, the c-Jun N-terminal kinase (JNK) signaling pathway functions crucially in regulating gene expression and intracellular metabolism in life activities, including growth and development, apoptosis and cellular response to external stress (20). Recently, the activation of the JNK signaling pathway was reported to mediate thyroid dysfunction re sulting from thyroid inflammatory responses and polychlorinated biphenyls (21). Based on existing knowledge, gene expression microarray analysis was performed to screen differentially expressed genes (DEGs) associated with TC and determine an unclarified gene, LRRK2, associated with TC.…”
Section: Introductionmentioning
confidence: 99%